Standing on the shoulders of a criminological giant: Steven Box and the question of counter-colonial criminology - Agozino, Biko (Demystifying power, crime and social harm, 2023)
This chapter focuses on the exploration of the assumption by Steven Box, (Power, Crime and Mystification, Tavistock, London, 1983, hereafter, PCM) that power and not powerlessness is a major cause of crime. The chapter starts by revisiting an earlier debate by Box and Ford (Sociological Review 19:31–52, 1971) as a background to understanding the importance of the original contribution to knowledge made by Box (PCM ower). A reading of Chapter One of PCM shows that Box understood the importance of including crimes by states especially in formerly colonized countries under imperialism today, indirectly calling for decolonization struggles to carry on. The issues about PCM in relation to colonialism and state violence have, to the best of our knowledge, not been developed in the depth that they should be. So the chapter develops the following themes: in what ways could Box’s thesis be applied to the crimes and social harms of slavery, colonialism, apartheid, internal colonialism and neocolonialism; how have these crimes been mystified, what about the nature of the power exercised by the rapacious colonial state in alliance with imperialist corporations and how can a Counter-Colonial Criminology (Agozino, 2003) be utilized to contest/resist the mystification process Box identified so powerfully 40 years ago?